Positive PsychoTherapy in ABI Rehab (PoPsTAR): A pilot randomised controlled trial. Issue 1 (2nd January 2018) - Cullen, Breda; Pownall, Jaycee; Cummings, Joanne; Baylan, Satu; Broomfield, Niall; Haig, Caroline; Kersel, Denyse; Murray, Heather; Evans, Jonathan J.
ABSTRACT: Psychological distress is common following acquired brain injury (ABI), but the evidence base for psychotherapeutic interventions is small and equivocal. Positive psychotherapy aims to foster well-being by increasing experiences of pleasure, engagement and meaning. In this pilot trial, we investigated the feasibility and acceptability of brief positive psychotherapy in adults with ABI and emotional distress. Participants were randomised to brief positive psychotherapy plus usual treatment, or usual treatment only. Brief positive psychotherapy was delivered over eight individual out-patient sessions, by one research psychologist. A blinded assessor administered the Depression Anxiety Stress Scales (DASS-21) and the Authentic Happiness Inventory (AHI) at 5, 9 and 20 weeks post-baseline. Of 27 participants randomised (median age 57; 63% male; 82% ischaemic stroke survivors; median 5.7 months post-injury), 14 were assigned to positive psychotherapy, of whom 8 completed treatment. The intervention was feasible to deliver with excellent fidelity, and was acceptable to participants. Retention at 20 weeks was 63% overall. A full-scale trial would need to retain n  = 39 per group to end-point, to detect a significant difference in change scores on the DASS-21 Depression scale of 7 points (two-tailed alpha = .05, power = .80). Trials including an active control arm would require larger sample sizes. We conclude that a full-scale trial to investigate efficacy is warranted.